Dectin-1/IL-15 Pathway Affords Protection against Extrapulmonary Aspergillus fumigatus Infection by Regulating Natural Killer Cell Survival - Fábio S.Y. Yoshikawa; Maki Wakatsuki; Kosuke Yoshida; Rikio Yabe; Shota Torigoe; Sho Yamasaki; Glen N. Barber; Shinobu Saijo (Karger Publishers, 2023)
Aspergillus fumigatus is a ubiquitous, yet potentially pathogenic, mold. The immune system employs innate receptors, such as dectin-1, to recognize fungal pathogens, but the immunological networks that afford protection are poorly explored. Here, we investigated the role of dectin-1 in anti-A. fumigatus response in an experimental model of acute invasive aspergillosis. Mice lacking dectin-1 presented enhanced signs of inflammation, with increased production of inflammatory cytokines and neutrophil infiltration, quickly succumbing to the infection. Curiously, resistance did not require T/B lymphocytes or IL-17. Instead, the main effector function of dectin-1 was the preservation of the NK cell population in the kidneys by the provision of the cytokine IL-15. While the depletion of NK cells impaired host defense in wild-type mice, IL-15 administration restored antifungal responses in dectin-1-deficient mice. Our results uncover a new effector mechanism for dectin-1 in anti-Aspergillus defense, adding an alternative approach to understand the pathophysiology of this infection.